Transformation of Education in The Era 5.0: Challenges of Innovation and Opportunities for Change - Marlinton, Melisa (Proceedings International Conference on Education Innovation and Social Science, 2023)
The rapid advancement of technology has ushered in Era 5.0, characterized by a highly interconnected and intelligent society. This era poses challenges and opportunities for the field of education, requiring a transformative approach to meet the evolving needs of learners and society. This study employed a literature review methodology to explore the challenges faced by educational systems in Era 5.0 and identify potential opportunities for innovation and change. The findings underscore the importance of educational institutions embracing innovation and adaptability to address the demands of Era 5.0. This includes integrating emerging technologies like artificial intelligence, virtual reality, and data analytics into teaching and learning processes. Furthermore, the study emphasizes the significance of fostering critical thinking, creativity, collaboration, and other 21st-century skills in students to prepare them for future challenges and opportunities. In conclusion, this research sheds light on the transformative potential of education in Era 5.0. Embracing these transformations empowers educational systems to equip learners with the necessary skills to thrive in a rapidly evolving society and contribute to its sustainable development.